DEVELOPING AN ENGLISH SYLLABUS FOR D3 CIVIL ENGINEERING STUDENTS OF ITS SURABAYA - Umi Trisyanti (Jurnal Sosial Humaniora, 2025)
The objective of this study is to develop the English syllabus for D3 Civil Engineering Department. The subjects, therefore involves the students, the subjects specialist, and the English teachers. To get the data of students needs, the questionnaire, interview, document and observation were implemented. Research and Development (R & D) was adopted as the research design, while the model of the development was Language Program Development by Yalden. The most important stage in this study is the needs survey to find out the real needs and interest of those involved in the program as it is the bases for the development. The needs survey was done by distributing questionnaires to the students, subject specialist and the English teachers as the subject of the study. They were asked to respond to the questionnaires. As the product will be implemented in the D3 Civil Engineering program, the syllabus should be validated by the expert in the syllabus design as well as the teacher of the department who has the mastery of the content to check the appropriateness of the topics in the syllabus with the subjects of the field being discussed. Revision was made based on the comments and suggestions given by the experts. Further verification was conducted by trying out the syllabus to the English teachers to make lesson plans based on the proposed syllabus. Based on the findings of needs survey and the result of the development, some suggestions are recommended. ESP is different from general English and it needs careful preparation in the teaching and learning process. English teachers should always collaborate with the subject specialist in determining the syllabus and the material